Annual Daylight Performance of Perforated Screen Facade in Loft Office in the Tropics - Feny Elsiana; Danny S. Mintorogo (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2025)
Implementing daylighting in office buildings offers energy savings and psychological and physiological benefits for occupants. One type of office currently developing in Indonesia is the loft office, which is characterized by a mezzanine floor, a high ceiling, and a fully glazed facade. Without adequate shading, buildings with fully glazed facades are at risk of excessive daylight exposure and glare issues. Perforated Screen Facade (PSF) is one of the shading devices that can reduce excessive daylight level and glare while still allowing daylight penetration. The research aim is to evaluate the annual daylight performance of PSF implementation with different perforation percentages in loft offices in the tropics. The research method is experimental and uses a radiance-based daylighting simulation. The useful daylight illuminance (UDI) and spatial disturbing glare (sDG) of a loft office with a fully glazed facade were compared to a loft office equipped with a PSF with different perforation percentages. The integration of a PSF reduces UDI excessive and sDG while improving UDI100-3000lx in areas near the glazed facade. Considering the importance of glare reduction in tropical climates, a loft office with a PSF perforation percentage of 20% was selected as the optimum configuration for annual daylight performance.